Biology of Myelomonocytic Cells - Ghosh, Anirban (IntechOpen, 2017)
Myelomonocytes are the multipotent cells in the stage of blood cell differentiation, which mainly comprise blood monocytes, tissue macrophages and subset of dendritic cells. Actually, their position and ability of judgement of the health of tissue or organ environment are the key initiators of tissue-specific immune response in a local and global fashion. Interestingly, the morpho-functional aspects of this group of cells vary to a wide range with their positional diversity. Their ability to communicate or represent the tissue microenvironment to the peripheral immune system and efficiency to engage the system to effector activation hold the key for a successful immune endeavour. The present volume shows some glimpses of such an extensive area of current immunology research.